2016
DOI: 10.1088/0963-0252/25/5/054006
|View full text |Cite
|
Sign up to set email alerts
|

Matching a (sub)nanosecond pulse source to a corona plasma reactor

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…Wang et al report yields as high as 239 g•kWh −1 ‡ with their nanosecond pulse source and show in an extensive map the comparisons between different discharge methods and the very good results of nanosecond pulsed discharges [49]. In [50] we already showed that the ozone yield with our nanosecond pulse source and our coronaplasma reactor can reach 170-190 g•kWh −1 , indicating that we obtain very high ozone yields as well.…”
Section: Plasma Processessupporting
confidence: 58%
“…Wang et al report yields as high as 239 g•kWh −1 ‡ with their nanosecond pulse source and show in an extensive map the comparisons between different discharge methods and the very good results of nanosecond pulsed discharges [49]. In [50] we already showed that the ozone yield with our nanosecond pulse source and our coronaplasma reactor can reach 170-190 g•kWh −1 , indicating that we obtain very high ozone yields as well.…”
Section: Plasma Processessupporting
confidence: 58%
“…This connection is made with a cable coupler, that was designed to be impedance matched to the coaxial cable and was introduced in [65].…”
Section: Plasma Reactor and Imaging Systemmentioning
confidence: 99%
“…7 consists of the 1-m reactor model and two transmission lines that represent the SA24272 cable. These transmission lines are ideal These waveforms were taken from the experiments of [65].…”
Section: Spice Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This connection is made with a cable coupler, that was designed to be impedance matched to the coaxial cable and was introduced in Ref. 29.…”
Section: B Plasma Reactormentioning
confidence: 99%